Effect of Thermoelectric Power and Air Flow on Air Temperature and Relative Humidity - Arasy Fahruddin; Prantasi Harmi Tjahjanti; Mulyadi (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering))
A dehumidifier is a device for drying air by releasing moisture. A dehumidifier with a thermoelectric cooler has the advantage of being more compact and has the potential to be combined with an air heater. This study aimed to determine the effect of thermoelectric power and airflow on air temperature and relative humidity. The research method uses direct experiments with six pieces of thermoelectric as a coolant. The data taken are the cooler surface temperature, the air temperature that is dried, and the humidity of the air. The test results show that the dried air temperature can reach 25.6oC with 78% humidity in environmental conditions with an ambient air temperature of 31oC.